Measurement of power line sagging using sensor data of a power line inspection robot - Zengin, Aydın Tarık; Erdemir, Gökhan; Akinci, Tahir Cetin; Seker, Serhat (Ieee-Inst Electrical Electronics Engineers Inc, 2020)
The operation of energy transmission lines with high efficiency without failure has great importance in today & x2019;s electricity-dependent world. Problems that may occur in electricity transmission lines are failure cause of many operations not only industrial but also daily life. One of the most important causes of the problems encountered in power lines is the change in the amount of sagging. The change of sagging amount causes line breaks and losing energy efficiency. This problem, which is frequently encountered due to seasonal and climatic changes, is one of the major problems of continuity in the power line. The calculation of sag contains uncertain and variable parameters that can change seasonally, climatically and/or structurally such as weight per unit length of the conductor, the horizontal component of tension, total tension, etc. In this case, it is difficult to calculate a precise and reliable sag amount. The sagging of power lines is generally calculated theoretically or measured on-site by the personnel in charge. In this study, a new approach is presented to measure the sag amount by using sensor data of a power line inspection robot, precisely and reliably. The inspection robot moving on the power line can be remotely controlled and send sensor data. The sagging is measured with an error of less than 2 percent in the laboratory test field by using this technique.
WOS:000541127800022
Keywords: Power transmission lines; Robot sensing systems; Transmission line measurements; Inspection; Mathematical model; Conductors; Power line inspection; line sag; line inspection robot